YOGA SURYA NAMASKARA SEBAGAI MEDIA MENINGKATKAN IMAN DAN IMUN DI MASA PANDEMI COVID -19 - Nengah Artawan; Komang Agus Triadi Kiswara (UNHI PRESS, 2021)
Yoga is a sport that involves both physical and psychological. Defining yoga, Yoga Citta Vertti Nirodha. that is, controlling thought movements, or ways to control the behavior of thought patterns that tend to be wild. In facing global challenges, young Hindus must be fortified with religious values ​​so that they are able to understand and realize the religious teachings contained in the Hindu scriptures as a reflection in people's lives during the Covid-19 pandemic. Of course, this challenge becomes very difficult considering the current COVID-19 outbreak that has hit almost all corners of the country. Restrictions on various activities will certainly have an impact on the attitudes of the younger generation, especially in relation to the cultivation of religious values. On the other hand, as a form of preventing the spread of COVID-19, an effort is needed to increase the body's immunity. Therefore, an effort is needed that can increase faith and also the body's immune. One solution is to do Surya Namaskara Yoga.Surya Namaskara Yoga is very important to do as a way to live healthy (immune) and spiritual (faith). Based on this thought, the article is presented, because Surya Namaskara Yoga is able to increase faith and immunity during the covid -19 pandemic, because yoga asana is a perfect sadhana, which consists of asanas, pranayama, and meditation techniques. During the COVID-19 pandemic, you must be able to do sports, breath, and taste to increase your faith and immunity. The logical method used in this research is a qualitative method where the data collected is presented in a descriptive way. The results of this study are these reveal as follows; (a) health, (b) self-control, (c) spiritual awareness. Surya Namaskara Yoga is an activity that connects and unites body movements, breathing exercises, and concentration of mind to gain faith and immunity. Yoga is a practical way of realizing the teachings of Tattwa Jnana. Asana-Pranayama-Pratyahara-Dharana-Dhyana-Taraka-Samadhi.